A COMPARISON OF THE EFFECT OF THE PRACTICETEACHING STYLE AND COMMAND TEACHING STYLETOWARDS HIGH SCHOOL STUDENTS’ ABILITY TO BACK ROLL - Muhamad Rohadi (CENDIKIA, 2019)
This study aims to compare the effect of the practiceteaching style and command teaching style approach on the high school students’ ability in back rolls. This research used the experimental method. Sampling in this study used the purposive sampling technique which was conducted on 40 students. There are 2 main variables: (1) the independent variable is the teaching method, (2) the dependent variable is the back roll ability. The data analysis technique used in this study was the difference test or t-test with a significance level of 0.05. The results showed that there was a significant difference between the method ofpracticeteaching style and command teaching style with the tcountresults of 5.230> t table 1.686 or sig 0.000 <α 0.05. The conclusion of this study is that there is a difference between the method of practiceteachingstyle approach and command teaching style on the ability to back roll in physical education learning in learning floor gymnastics. The practiceteaching style is more recommended than command teaching style.